Work Posture Analysis Based on Posture Evaluation Index Case Study of PT XTZ Workshop Department - Pratama, Ardand Putra; Sulaiman, Mochamad; Karim, Abdul Alimul (Institut Teknologi Adhi Tama Surabaya, 2025)
Manual handling in workshop activities has the potential to cause greater injury to workers than moving goods with the help of tools. Therefore, this study conducted an analysis of the risk of occupational diseases using the PEI method in the workshop department with the aim of evaluating the work posture of workers in Manual Material Handling activities. The simulation with Technomatic Jack 8.4 software that has been run shows the calculation of the PEI value based on the LBA, OWAS, and RULA values in 10 manual handling movements. It was found that there were two movements that had a PEI value of more than 2 (Middle - Low Injury) which means it is dangerous if it continues to be done, both movements include movements when lifting the breakdrum and when moving the breakdrum, the LBA obtained has a value exceeding the NIOSH standard of 3400 N, in the same movement the OWAS produced is worth 4 and 3, and RULA in the same movement has a value of 7. So that in the movements when lifting the breakdrum and when moving the breakdrum, work improvements are needed to avoid injury.